Pengaruh Pijat Bayi untuk Meningkatkan Status Kesehatan Anak Bayi 1-12 Bulan - Aryunani Aryunani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to identify the effect of infant massage in improving the health status ofinfants 1-12 monthsMethods: This study is a pre-experimental study with one group-test pre-post testdesign This study uses an observation sheet where baby weight weighing is carriedout before the baby massage (Pretest) and after the baby massage (Posttest) in thegroup is carried out. Massage is done 2 times / week during 10- 15 minutes for 4weeks assessed with a checklist sheet. The unit of analysis is children under oneyear old totaling 30 babies. Wilcoxon Test Sample analysis, which is to determinethe difference in treatment in two samples / treatment groups on the condition thatthe data is normally distributed.Results: complaints of babies aged 1-12 months before stimulation of babymassage, most of the respondents had complaints experienced by babies wererunny nose (40%), cough (30%), fever (27%) and no complaints (7%) and after ababy massage, complaints of colds were 5 respondents (16%), cough 2 respondents(7%), and heat respondents of 1 person (4%) and no complaints (73%).Researchers conducted a statistical test wilcoxon obtained a significant figure(0.000) much lower than a significant standard of 0.05, which means that there isan effect of Massage on the health status of babies aged 1-12 months at PMB SitiAlfiyah SurabayaConclusion: In this study, it was concluded that there was a significant influence ofgiving baby massage on the health status of babies at the age of 1-12 months.Researchers found complaints such as cough, runny nose, higher heat occurred inbabies before baby massages